Targeting human inducible regulatory T cells (Tr1) in patients with cancer: blocking of adenosine-prostaglandin E(2) cooperation - Mandapathil, M. (2011)
INTRODUCTION: Emerging data suggest that human inducible Treg (Tr1) produce adenosine and prostaglandin E(2) and that these factors cooperate in mediating immune suppression. AREAS COVERED: Human Tr1 present in human tumors or blood of cancer patients express ectonucleotidases, CD39 and/or CD73, hydrolyze ATP to adenosine and are COX-2(+). Expression of CD39 and/or CD73 on human tumors favors expansion and suppressor functions of Tr1. Adenosine and PGE(2) signal via A(2A)R and EP(2)R expressed on effector T (Teff) cells, suppressing their anti-tumor functions by a common mechanism involving up-regulation of cytosolic cAMP levels and PKA type I activation. The frequency and activity of circulating CD4(+)CD39(+) and CD4(+)COX-2(+) Treg subsets increase in advanced disease and also following oncologic therapies. EXPERT OPINION: Pharmacologic blocking of adenosine/PGE(2) collaboration provides a clinically-feasible strategy for disarming of Treg. Used in conjunction with conventional anti-cancer drugs or immune interventions, pharmacologic inhibitors could improve outcome of oncologic therapies.